Sodelovanje med slovenskim in italijanskim osvobodilnim gibanjem v vzhodni Furlaniji v obdobju med septembrom 1943 in oktobrom 1944 - Troha, Nevenka (Prispevki za novejšo zgodovino, 2022)
The following article focuses on the cooperation between the Slovenian and Italian liberation movements in the area of eastern Friuli from the Italian capitulation to the autumn of 1944. At that time, cooperation was crucial for the liberation efforts due to the still overwhelming strength of the occupiers. However, as of the autumn of 1944 – in anticipation of the imminent end of the war and the consolidated position of the Yugoslav liberation movement – the Slovenian liberation movement sought to establish complete control of the areas populated by Slovenians and thus strengthen the Yugoslav position in the post-war negotiations on the new border with Italy.
Keywords: boj za meje; Briškobeneški odred; druga svetovna vojna; enote Garibaldi; Furlanija; Italija; Jugoslavija; komunisti; konec vojne; odporniško gibanje; Osoppo; partizanske enote; slovensko-italijanski odnosi